Effect of Addition of Stone Dust as Fine Aggregate on Properties of Concrete Containing Rice Husk Ash as Cement Replacement - Oberoi, Navdeep Singh (My University, 2015)
River sand is most commonly used fine aggregate in the production of concrete poses the problem of acute shortage in many areas. The continuous use of river sand has started posing serious problems with respect to its availability, cost and environmental impact. In such a situation the Quarry rock dust or stone dust can be an economic alternative to the river sand. This thesis aims to find the possibility of the structural usage of stone dust as a fine aggregate as an alternative or mixed in different proportion with natural aggregates. Rice husk ash is used as additional cementing material. A comprehensive literature review is carried out for better understanding of mechanical properties of concrete containing stone dust as fine aggregate and rice husk ash as a cement replacement. The mixes of M30 grade concrete was prepared with normal sand, stone dust and combination of normal sand and stone (50%-50%) as a fine aggregate. Additional cementing material i.e. rice husk ash was used as a cement replacement with 0%, 10%, 20% and 30% substitution by weight of cement. Tests were conducted on cubes to study the strength of concrete made of Quarry Rock Dust and the results were compared with the Natural Sand Concrete. Primarly, fresh properties, mechanical properties (compressive strength), durability properties (water sorptivity), along with microstructure analysis with XRD and SEM is discussed in the present study. The tests results revealed that Physical and chemical properties of quarry rock dust satisfies the requirements of Indian Standard code provision for fine aggregate and hence, can be used as possible replacement of fine aggregate. The slump values within the desired range of 50-75 mm were observed for all the mixes. The Slump value increases with increase in percentage replacement of sand with quarry dust for the same w/c ratio and decreases with the addition of rice husk ash as a cement replacement. The compressive strength of concrete made with stone dust increases up to 73% as compare to concrete made with normal sand. Sorptivity of the concrete decreses with addition of stone dust and rice husk ash. Microstructer analysis revealed that there is also no qualitative change in phases present in concrete on replacement of natural sand with stone dust and cement with rice husk ash. The mix made with stone dust has dense CSH gel forma
M.E. (Structural Engineering)
Keywords: Stone Dust; Rice Husk Ash; CED